T 1 EFFECT OF FEEDING TE ON THE GROWTH, FOOD CONVERSION PROTEIN EFFICIENCY OF SILVER DOLLAR, METYNNIS SCHREITMULLERI ( L), FRY - Singh, R. K.; Vartak, V. R.; Balange, A. K.; Chavan, J. B. (Journal of Indian Fisheries Association, 2015)
A 30-day experiment was conducted to determine the effects of varying feeding rates on the growth of fry of silver dollar, Metynnis schreitmulleri (Ahl). Silver dollar fry with an average initial body weight of 1.100 Â± 0.029g were collected from a local fish breeder and fed a diet (35% protein and 6% fat) at the rate of 3, 6 and 9% of body weight per day in two equal meals. Per cent weight gain increased from 54.54 to 118.18 with increased feeding rates, which were significantly different (p<0.05) from each other. The highest specific growth rate was obtained’ in the fry fed at 9% body weight per day. In another study for 30 days, the effects of feeding frequency on growth, feed conversion and protein efficiency of silver dollar fry were evaluated. Groups of silver dollar fry with an initial individual weight of 0.700 Â± 0.019 g were offered feed continuously for 24 hours during the day or night at different time intervals with varying meal sizes. The night time feeding with two meals gave the lowest weight and length gains (0.985 g and 0.30 cm). The growth rates of fish fed during day with three equal-sized meals are significantly (p<0.05) higher (4.66%) than the other treatments. Keywords: Silver dollar, feed ration, feeding frequency